Electrophoretic build-up of alternately multilayered films and micropatterns based on graphene sheets and nanoparticles and their applications in flexible supercapacitors - Zhou, Weiya (2013)
Graphene nanosheets and metal nanoparticles (NPs) have been used as nano-building-blocks for assembly into macroscale hybrid structures with promising performance in electrical devices. However, in most graphene and metal NP hybrid structures, the graphene sheets and metal NPs (e.g., AuNPs) do not enable control of the reaction process, orientation of building blocks, and organization at the nanoscale. Here, an electrophoretic layer-by-layer assembly for constructing multilayered reduced graphene oxide (RGO)/AuNP films and lateral micropatterns is presented. This assembly method allows easy control of the nano-architecture of building blocks along the normal direction of the film, including the number and thickness of RGO and AuNP layers, in addition to control of the lateral orientation of the resultant multilayered structures. Conductivity of multilayered RGO/AuNP hybrid nano-architecture shows great improvement caused by a bridging effect of the AuNPs along the out-of-plane direction between the upper and lower RGO layers. The results clearly show the potential of electrophoretic build-up in the fabrication of graphene-based alternately multilayered films and patterns. Finally, flexible supercapacitors based on multilayered RGO/AuNP hybrid films are fabricated, and excellent performance, such as high energy and power densities, are achieved.